Towards Precision Vaccines: Lessons From the Second International Precision Vaccines Conference - Soni, Dheeraj; Van Haren, Simon D.; Idoko, Olubukola T.; Evans, Jay T.; Diray-Arce, Joann; Dowling, David J.; Levy, Ofer (Frontiers in Immunology, 2020)
Other than clean drinking water, vaccines have been the most effective public health intervention in human history, yet their full potential is still untapped. To date, vaccine development has been largely limited to empirical approaches focused on infectious diseases and has targeted entire populations, potentially disregarding distinct immunity in vulnerable populations such as infants, elders and the immunocompromised. Over the past few decades innovations in genetic engineering, adjuvant discovery, formulation science and systems biology have fueled rapid advances in vaccine research poised to consider demographic factors (e.g., age, sex, genetics and epigenetics) in vaccine discovery and development. Current efforts are focused on leveraging novel approaches to vaccine discovery and development to optimize vaccinal antigen and, as needed, adjuvant systems to enhance vaccine immunogenicity while maintaining safety. These approaches are ushering in an era of precision vaccinology aimed at tailoring immunization for vulnerable populations with distinct immunity. To foster collaboration among leading vaccinologists, government, policy makers, industry partners and funders from around the world, the Precision Vaccines Program at Boston Children’s Hospital hosted the 2nd International Precision Vaccines Conference (IPVC) at Harvard Medical School on the 17th-18th October 2019. The conference convened experts in vaccinology, including vaccine formulation and adjuvantation, immunology, cell signaling, systems biology, biostatistics, bioinformatics, as well as vaccines for non-infectious indications such as cancer and opioid use disorder. Herein we review highlights from the 2nd IPVC and discuss key concepts in the field of precision vaccines.